Polemik Salakanagara: Meninjau Kebenaran Bukti Historis Salakanagara dalam Pentas Sejarah Kuno di Indonesia - Wildhan Ichzha Maulana (Universitas Negeri Padang, 2023)
This study aims to analyze historical evidence and the views of the Banten people towards the existence of the Salakanagara Hindu kingdom. The research method used is a historical method covering 4 stages, namely heuristics, verification, interpretation, and historiography which is supported by a correspondence theory framework to explore the historical truth of Salakanagara based on the support of objective facts in the form of written sources and archaeological remains. The results of this study indicate that (1) the historical facts of Salakanagara are not supported by strong primary historical sources such as findings of inscriptions, archaeological remains, literary works, and contemporary foreign chronicles. (2) The historical facts of the new Salakanagara are based on the Wangsakerta manuscript whose validity is still widely doubted, then myths and legends, in which the three incidentally are secondary historical sources. (3) The majority of Bantenese people believe that Salakanagara was once founded, but this view arises from attribution to historical sources which are less valid and relevant. Therefore, Salakanagara's studies are still limited to historical hypotheses, because they are only supported by the truth from secondary historical sources. However, it also does not rule out the possibility that stronger primary historical sources are found in its development so that the historical facts of Salakanagara can be legally recognized.